The knowledge level and influencing factors of sarcopenia among Chinese community-dwelling older adults - Wanyue Guo; Tianya Wang; Huohuo Dai; Yuqi Wang; Zihan Zhou; Ye Wang; Xianbo Pei; Qing Zhang (PLoS ONE, 2025)
Aim This study aimed to assess the knowledge level of sarcopenia and its influencing factors among Chinese community-dwelling older adults. Methods We conducted a cross-sectional study using the sociodemographic questionnaire, the Sarcopenia Knowledge Awareness Survey Scale and the SARC-CalF scales for data collection in 5 communities in Wuhan, Hubei Province, China. Influencing factors of sarcopenia knowledge were analyzed by logistic regression, and a decision tree model. Results A total of 569 participants were included in the analysis. Only 17.8% participants had heard of sarcopenia, 19.3% of participants screened positive for sarcopenia, and 29.0% had a self-assessed muscle status that was inconsistent with the actual screened sarcopenia status. Those aged 75 years and above were more likely to have inadequate sarcopenia knowledge (OR=0.468,95% CI = 0.303–0.723). The group with the highest proportion of low sarcopenia knowledge consisted of those who lived alone or with children, had an education level of middle school or below, and never engaged in any social activities (97.6%). Conclusions Knowledge of sarcopenia among older adults in Chinese communities is still inadequate. Further tailored interventions may help to ameliorate this lack of knowledge.